Existential Struggles in Nigeria and Social Movement Theory: Case Study of #ENDSARS - Ifeoma, Charles-Monwuba (Journal of Leadership, Accountability and Ethics, 2023)
Existential struggles appear to be unending in developing nations, including Nigeria. Some of the existential struggles lead to citizen agitations and evolve into social movements, some of which have recorded varying success rates. This paper thus seeks to examine #ENDSARS protests as a case study vis-à-vis the social movement theory. It explores the theory to provide meaning to what happened with #ENDSARS, outcomes and recommendations for future social movements or otherwise. Findings indicate that New Social Movement Theory (NSMT) played out effectively during the #ENDSARS protest, with technology driving all the attributes of the social movement theory. As a recommendation, the policymakers must approach issues affecting the welfare and livelihoods of its citizens carefully before it snowballs into agitations like the #ENDSARS protest. Government must balance the need for fiscal responsibility and economic growth with the need to protect the interests of ordinary Nigerians and ensure social stability. Theorists must hereafter review new theories against contemporary realities and technological potential.